The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1371/journal.pone.0100925
|View full text |Cite
|
Sign up to set email alerts
|

How to Boost Positive Interpretations? A Meta-Analysis of the Effectiveness of Cognitive Bias Modification for Interpretation

Abstract: The current meta-analysis explores the strength of effects of cognitive bias modification training for interpretation bias (CBM-I) on positive (i.e., adaptive) interpretations and mood as well as the training and sample characteristics influencing these effects. Data-bases were searched with the key words “interpret* bias AND training” and “interpret* bias AND modif*”. Reference lists of identified articles were checked and authors of identified articles were contacted for further relevant articles and unpubli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

19
157
1
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(181 citation statements)
references
References 73 publications
19
157
1
4
Order By: Relevance
“…Firstly, no study to date has investigated the isolated effects of CBM-I for OCD over multiple sessions of training. Several studies have demonstrated that CBM-I can reliably alter individuals' interpretive bias, however more than one session of CBM training will likely be required for significant changes on downstream measures of psychopathology to be observed (MacLeod et al 2009;Menne-Lothmann et al 2014). Additionally, no study investigating the isolated effects of CBM-I for OCD has employed the training in a nonlaboratory setting.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, no study to date has investigated the isolated effects of CBM-I for OCD over multiple sessions of training. Several studies have demonstrated that CBM-I can reliably alter individuals' interpretive bias, however more than one session of CBM training will likely be required for significant changes on downstream measures of psychopathology to be observed (MacLeod et al 2009;Menne-Lothmann et al 2014). Additionally, no study investigating the isolated effects of CBM-I for OCD has employed the training in a nonlaboratory setting.…”
mentioning
confidence: 99%
“…Expert commentators have suggested that conducting training in more naturalistic contexts may augment the impact of CBM (MacLeod and Mathews 2012). Thirdly, studies with follow-up measures several days or weeks after training are necessary to allow participants time to consolidate and implement their new learning (Clerkin and Teachman 2011;Menne-Lothmann et al 2014).…”
mentioning
confidence: 99%
“…Similarly, our findings could be relevant in the context of cognitive bias modification where the aim is to override habitual ways of processing of emotional information. For example, a recent meta-analysis on the effectiveness of cognitive bias modification procedures to train towards a benign interpretation bias shows that the use of imagery was related to larger cognitive and emotional effects [36].…”
Section: Discussionmentioning
confidence: 99%
“…Por ejemplo, en el caso de la MSC-I en trastornos emocionales, el meta-análisis de Menne-Lothmann et al (2014) indica que el procedimiento es efectivo para reducir tanto sesgos como sintomatología y que los resultados son mejores para las mujeres. Asimismo, algunos estudios concluyen que la MSC es más eficaz en personas con depresión leve (Baert, De Raedt, Schacht y Koster, 2010;Yiend et al, 2014).…”
Section: Discussionunclassified
“…Dado que en la mejora del aprendizaje humano es esencial proporcionar feedback sobre las respuestas del individuo (Hays, Kornell y Bjork, 2010), los procedimientos de entrenamiento deberían incluir en la medida de lo posible feedback sobre el rendimiento del participante en tiempo real. Esto no ocurre en la mayor parte de los estudios de entrenamiento a pesar de que la evidencia existente sugiere que este factor potencia la reducción de los sesgos cognitivos, aunque quizás no sea tan relevante para la mejora del estado emocional (Menne-Lothmann et al, 2014). Otro aspecto que todavía queda por esclarecer es si es conveniente que el individuo conozca la contingencia del entrenamiento.…”
Section: Discussionunclassified